Growth of the Southern Patagonian Andes (46 -53°S) and its relation with subduction processes - Ghiglione, Matias; Ramos, Victor Alberto; Cuitiño, José Ignacio; Barberon, Vanesa
The Cretaceous-Cenozoic evolution of the Southern Patagonian Andes is one of the most prominent examples of coupling between subduction processes and climatic, magmatic, deformational, and sedimentary events. Three orogenic and magmatic cycles can be particularly related to processes in the subduction zone (1) Late Cretaceous closure of the Rocas Verdes marginal basin, (2) Paleogene collisionof the Farallón-Aluk seismic ocean ridge, and (3) Miocene subduction of the Chile seismic ridge beneath South America. Andean orogenic growth started during Late Cretaceous times, in a tectonic scenario that included the Rocas Verdes back-arc oceanic basin, widening from 49°S toward the south. The Andean segment south of 49°S experienced a strong Cenomanian?Santonian deformational event during theclosure of the back-arc basin and progressive subduction of its ocean floor. The final closure produced the Coniacian?Santonian exhumation of the Sarmiento Ophiolitic Complex and propagation of the orogenic front toward the foreland. The second cycle, during Paleogene deformation, coincided with an Eocene volcanic arc gap, and seems to be related to the Fallarón-Phoenix seismic ridge collision. The resulting slab window produced OIB volcanic plateaux represented by the Chile Chico and Posadas Basalts, erupted in the foothills and retroarc. The third cycle of accelerated Andean uplift started during the Oligocene, as a consequence of orthogonal and fast subduction of young lithosphere, while the Chile seismic ridge between Antarctica and Nazca was approaching the trench. Kinematic plate reconstructions show that at approximately 14?18 Ma the Chile oceanic ridge entered the South America trench and migrated northward from 53°S to its present-day position at 46°S. The early Miocene ridge collision and resulting slab window produced an extensive OIB magmatism between 10 and 3 Ma in extra-Andean Patagonia. The space-time unraveling of tectonic uplift is well known from geochronometers, and shows a migration from the basement domain to ...